Saving of water and labor in a rice-wheat system with no-tillage and direct seeding technologies - Bhushan, Lav; Ladha, Jagdish K.; Gupta, Raj K.; Singh, S.; Tirol-Padre, A.; Saharawat, Y.S.; Gathala, M.; Pathak, H. (Wiley, 2007)
Conventional tillage and crop establishment methods such as puddled transplanting in the rice–wheat (Oryza sativa L.–Triticum aestivum L.) system in the Indo‐Gangetic Plains (IGP) require a large amount of water and labor, both of which are increasingly becoming scarce and expensive. We attempted to evaluate alternatives that would require smaller amounts of these two inputs. A field experiment was conducted in the IGP for 2 yr to evaluate various tillage and crop establishment systems for their efficiency in labor, water, and energy use and economic profitability. The yields of rice in the conventional puddled transplanting and direct‐seeding on puddled or nonpuddled (no‐tillage) flat bed systems were equal. Yields of wheat following either the puddled‐transplanted or no‐tillage direct‐seeded rice were also equal. Normally, puddled transplanting required 35 to 40% more irrigation water than no‐tillage direct‐seeded rice. Compared with conventional puddled transplanting, direct seeding of rice on raised beds had a 13 to 23% savings of irrigation water, but with an associated yield loss of 14 to 25%. Nevertheless, water use efficiency (WUE) in the rice–wheat system was higher with direct‐seeded rice (0.45 g L−1) than with transplanted rice (0.37–0.43 g L−1). In Year 1, no‐tillage rice–wheat had a higher net return than the conventional system, whereas in Year 2 the net returns were equal. The study showed that the conventional practice of puddled transplanting could be replaced with no‐tillage‐based crop establishment methods to save water and labor. However, the occurrence and distribution of rainfall during the cropping season had considerable influence on the savings in irrigation water.